Advancements and Complexities in the Conversion of Lignocellulose Into Chemicals and Materials - Fiorani, Giulia; Crestini, Claudia; Selva, Maurizio; Perosa, Alvise (Frontiers in Chemistry, 2020)
This Perspective describes the challenges and objectives associated to the development of new chemical technologies for the conversion of lignocellulose (non-food or waste) into chemicals and materials; it also provides an outlook on the sources, potential products and issues to be addressed.